If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 4 = 2p + 3 Reorder the terms: 4 + p = 2p + 3 Reorder the terms: 4 + p = 3 + 2p Solving 4 + p = 3 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 4 + p + -2p = 3 + 2p + -2p Combine like terms: p + -2p = -1p 4 + -1p = 3 + 2p + -2p Combine like terms: 2p + -2p = 0 4 + -1p = 3 + 0 4 + -1p = 3 Add '-4' to each side of the equation. 4 + -4 + -1p = 3 + -4 Combine like terms: 4 + -4 = 0 0 + -1p = 3 + -4 -1p = 3 + -4 Combine like terms: 3 + -4 = -1 -1p = -1 Divide each side by '-1'. p = 1 Simplifying p = 1
| 4+g/5=-7 | | x-.3333x=54 | | 3(x-4)+2=23 | | 2q+(-10)=108 | | 3y^2+5y-12=0 | | x-33.33x=54 | | 16y=-112 | | 5x/7+1/14+7/28 | | 16y=11 | | 2x^2+2x-96=0 | | r/3+6=42 | | 2/3x+5/6x+1/2x+10 | | -3(2x+11)=6x+33 | | 1/2(2x+3)+4x=5 | | 120=1.2x | | 2/3(4x-3)=2/5(x-4) | | 4(26-19)= | | y=x+(x*0.2) | | -11=18/5+s/5 | | 585.00+0.13x=850 | | -52-18= | | -2/3x=36 | | (p+12)/2=(8-3p)/4 | | 3y=4(2x-4) | | (-5m^6a^2/4m^-4a^-6)^-1 | | (18n^2-9n+1)/(3n-1) | | x-0.05x=418 | | 1/3(6x-9)=5 | | y=-11x-7 | | (x^2+3x-18)/(x-3) | | -4(y-7)=6y-12 | | 131.25/12.5 |